Car Key Lock Reminder - Zainol Amir Hafizuddin bin Zainol Abidin, Zainol Amir Hafizuddin (2010)
Car Key Lock Reminder is a conceptual system that reminds the user to lock their vehicle based on the current vehicle’s condition. The system calculates proximity distance between user and vehicle to determine whether the user is leaving the vehicle or not, before the system started to remind the user.